'How can we know the dancer from the dance?' Perspectives on Musicality in Human Movement. (May 2022) - Leslie-Spinks, Jeremy
Abstract : This paper presents the argument that inherent musicality in human movement is near-universal. I examine data and empirical evidence which suggest that dance, music, speech, and bipedalism are interrelated characteristics, rooted in the earliest moments of our history. The combination of proto-musical, rhythmic, tonal vocalisation and explanatory gesture has been suggested as the seminal beginning, both of dance and of language. This topic has been vigorously debated, indeed some twentieth-century studies dispute the universality of human musicality. Recent technological advances have, however, revealed data which support the case for innate, universal human musicality. I discuss possible reasons for adaptations for music, dance, and speech, and offer examples from neuroscience of our innate beat perception and entrainment ability, with consequent implications for dance as therapy and rehabilitation.